Chronic Thromboembolic Pulmonary Hypertension (CTEPH) and massive hemoptysis: The rationale for bronchial artery embolization. (April 2022) - Clements, Warren; Venn, Georgina; McGiffin, David; Moriarty, Heather K.; Joseph, Tim; Goh, Gerard S.; Whitford, Helen; Keating, Dominic
Abstract: Introduction: In many patients with Chronic Thromboembolic Pulmonary Hypertension (CTEPH), bronchial artery hypertrophy is observed. Patients with bronchial dilatation have been shown to be at increased risk of hemoptysis introducing the risk of airway obstruction. In this study from an academic tertiary referral center, we aimed to assess the incidence of massive hemoptysis in our CTEPH patients, the success of bronchial artery embolization (BAE), recurrence, and hemoptysis-related mortality. Methods: Retrospective cohort study of all adults with CTEPH who underwent BAE for massive hemoptysis between 1 January 2015 and 30 July 2021. Primary endpoints were hemoptysis relapse and hemoptysis-related mortality. Results: There were 367 patients who were being treated and managed with a diagnosis of CTEPH at our institution. There were 24 bronchial artery embolization procedures performed for all causes. A total of 3 patients during this time met inclusion criteria with acute massive hemoptysis and CTEPH. All patients were taking therapeutic-dose anticoagulation. Technical success after BAE was 100%. No hemoptysis recurrence was demonstrated at 17, 24, and 40-months follow-up respectively. No patient died from hemoptysis. However, 1 patient died 24 months after the embolization procedure due to a non-hemoptysis cause. Conclusion: This study highlights the low but important incidence of massive hemoptysis in patients with CTEPH. Unlike other causes of hemoptysis, this unique cohort requires balancing anticoagulation and hemorrhage control. Given the high degree of success, BAE is a viable option, allowing continuation or early re-establishment of anticoagulation. Highlights: Bronchial artery hypertrophy is observed in many patients with CTEPH. Retrospective review 367 CTEPH patients, 3 massive hemoptysis and bronchial artery embolization. Technical success 100%. No hemoptysis recurrence was demonstrated at follow-up. BAE in patients with CTEPH allows continuation or early re-establishment of anticoagulation.